Corrosion Inhibition Effect of 4-Hydroxy-N′-[(E)-(1H-indole-2-ylmethylidene)] Benzohydrazide on Mild Steel in Hydrochloric Acid Solution. (11th December 2014) - Kumari, Preethi; Shetty, Prakash; Rao, Suma A.
Abstract : The inhibition performance and adsorption behaviour of 4-hydroxy- N′ -[( E )-(1 H -indole-2-ylmethylidene)] benzohydrazide (HIBH) on mild steel in 1 M HCl solution were tested by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The inhibition efficiency of HIBH increases with increase in inhibitor concentration in the temperature range 30–60°C. Polarisation curves indicate that HIBH is a mixed inhibitor, affecting both cathodic and anodic corrosion currents. The adsorption process of HIBH at the mild steel/hydrochloric acid solution interface obeyed Langmuir adsorption isotherm model and inhibition takes place by mixed adsorption, predominantly chemisorption. The activation and thermodynamic parameters for the corrosion inhibition process were calculated to elaborate the mechanism of corrosion inhibition.